Thermal and Waterproof Properties of Foamed Concrete with Nano SiO2 Aerogel and Organosilicon Waterproofing Agent - Baojun Cheng; Xiaowei Gu; Yuxin Gao; Pengfei Ma; Shengrong Kang (Advances in Materials Science and Engineering, 2022)
This paper aimed to improve the thermal and waterproof properties of foamed concrete through the synergic work of nano SiO2 aerogel powder (NSAP) and organosilicon waterproofing agent (OWA). Hence, several series of foamed concrete with a 0–3.0% of OWA and with 1–4% of NSAP addition were developed. The results show that OWA can decrease the dry bulk density, compressive strength, water absorption rate, and thermal conductivity. With the addition of NSAP, the water absorption rate reached a minimum value of 9.2% at 3.0% NSAP, while the thermal conductivity continued decreasing. Through the microscopic pore size distribution, XRD, and SEM, it was found that the addition of NSAP had no effect on the type of hydration product, but it can increase the average pore size and the amount of macropore and weaken the interfacial adhesion between hydration products. Comparing the heat transmission model, the presence of NSAP increased the heat transmission pathway and resistance, resulting in lower thermal conductivity.